Differences in Glutathione Peroxidase (GPx) Levels Before and After Pulmonary Tuberculosis Treatment - Ersty Marthalia Putri; Anita Liliana Susanti; Deasy Wirasiti (Health & Medical Sciences, 2025)
This study aimed to review changes in glutathione peroxidase or GPx levels or activity before and after pulmonary tuberculosis treatment. A systematic scoping review was conducted on articles published between 2016 and 2025 retrieved from Google Scholar, ScienceDirect, and PubMed. Article selection followed PRISMA guidelines and applied eligibility criteria based on the PICO framework. Six studies met the inclusion criteria and were included in the analysis. All reviewed studies reported changes in GPx levels or activity after tuberculosis treatment, with most showing an increase in GPx activity following anti-tuberculosis therapy. Several studies also reported that adjunct antioxidant interventions, such as N-acetylcysteine, contributed to enhanced glutathione system function and increased GPx activity compared to standard therapy alone. The observed increase in GPx activity was associated with reduced oxidative stress and improved redox balance during treatment. These findings indicate that GPx has potential as a biomarker for monitoring treatment response in pulmonary tuberculosis. However, variations in study design, sample size, and measurement methods were identified across the included studies. Further well-designed clinical studies with standardized GPx assessment protocols are needed to confirm its clinical utility and to clarify the role of antioxidant supplementation in supporting tuberculosis treatment outcomes.